Digital literacy's role as a mediator in the impact of e-health literacy on sexual health literacy - Hacer Yalnız, Dilcen; Güleser Ada; Yasemin Bilişli; Yasin Özkara; Fatih Serdar Yıldırım; Serkan Say (Heliyon)
Sexual health literacy, e-health literacy, and digital literacy play pivotal roles in advancing safe sexual practices and facilitating access to sexual health services, particularly for young adults. The objective of this study is to explore how digital literacy serves as an intermediary role in the impact of e-health literacy on sexual health literacy. Employing a relational screening model within the framework of a general screening model, the study surveyed 601 literate individuals aged 18–25, who willingly participated. Research data were gathered using an introductory information form, Digital Health Literacy, Sexual Health Literacy, and E-Health Literacy scales. The findings indicate that digital health literacy serves as a partial intermediary factor in the relationship between e-health literacy and sexual health literacy. This study, the first of its kind, investigates the impact of e-health literacy on the sexual health literacy of young adults and examines the mediating role of digital literacy in this relationship. The research establishes an interconnected relationship among e-health literacy, digital literacy, and sexual health literacy, with digital literacy playing a mediating role in this connection. E-health literacy and digital literacy enhancement are crucial factors in improving public health by enabling young adults to access accurate information on sexual health.